Issues in drug metabolism of major antihypertensive drugs: β-blockers, calcium channel antagonists and angiotensin receptor blockers - Höcht, Christian (2010)
Several first-line antihypertensive drugs, including calcium channel blockers, beta-adrenergic blockers and angiotensin receptor blockers, undergo metabolism through different CYP isoforms. As a consequence of CYP-dependent metabolism, wide interindividual variability of plasma concentrations of antihypertensive drugs has been found in clinical practice compromising blood pressure lowering response and clinical outcomes. Several factors, including aging, hepatic impairment, drug interactions, conditions affecting hepatic blood supply and polymorphisms, contribute to changes in oral and systemic clearance affecting drug exposure during antihypertensive therapy and cardiovascular response. Considering that the degree of blood pressure reduction is related to antihypertensive drug plasma concentrations, a greater knowledge of the sources of pharmacokinetic variability of hepatically eliminated antihypertensive drugs and the applicability of an individualized approach in hypertension management by means of pharmacokinetic/pharmacodynamic modeling and pharmacogenetic testing could enhance blood pressure lowering response to pharmacological therapy. The aim of the present review is to discuss the relevance of drug metabolism in the treatment of hypertension.